Clinical and treatment outcomes of a second subcutaneous or intravenous anti-TNF in patients with ulcerative colitis treated with two consecutive anti-TNF agents: data from the ENEIDA registry - Margalida Calafat; Paola Torres; Joan Tosca-Cuquerella; Rubén Sánchez-Aldehuelo; Montserrat Rivero; Marisa Iborra; María González-Vivo; Isabel Vera; Luisa de Castro; Luis Bujanda; Manuel Barreiro-de Acosta; Carlos González-Muñoza; et al. (Therapeutic Advances in Gastroenterology, 2024)
Background: Infliximab seems to be the most efficacious of the three available anti-TNF agents for ulcerative colitis (UC) but little is known when it is used as the second anti-TNF. Objectives: To compare the clinical and treatment outcomes of a second subcutaneous or intravenous anti-TNF in UC patients. Design: Retrospective observational study. Methods: Patients from the ENEIDA registry treated consecutively with infliximab and a subcutaneous anti-TNF (or vice versa), naïve to other biological agents, were identified and grouped according to the administration route of the first anti-TNF into IVi (intravenous initially) or SCi (subcutaneous initially). Results: Overall, 473 UC patients were included (330 IVi and 143 SCi). Clinical response at week 14 was 42.7% and 48.3% in the IVi and SCi groups (non-statistically significant), respectively. Clinical remission rates at week 52 were 32.8% and 31.4% in the IVi and SCi groups (nonsignificant differences), respectively. A propensity-matched score analysis showed a higher clinical response rate at week 14 in the SCi group and higher treatment persistence in the IVi group. Regarding long-term outcomes, dose escalation and discontinuation due to the primary failure of the first anti-TNF and more severe disease activity at the beginning of the second anti-TNF were inversely associated with clinical remission. Conclusion: The use of a second anti-TNF for UC seems to be reasonable in terms of efficacy, although it is particularly reduced in the case of the primary failure of the first anti-TNF. Whether the second anti-TNF is infliximab or subcutaneous does not seem to affect efficacy.